Hubungan antara Tingkat Pendidikan Ibu dan Kecerdasan Logika-Matematika Siswa R.A. Muslimat N.U. Ponorog - Kurnia Hidayati (Nadwa: Jurnal Pendidikan Islam, 2013)
This study describes the relationship between mother's education level and students’ logic-mathematical intelligence at the RA NU 074 Ronowijayan Ponorogo. This study was conducted with a quantitative approach through the study of documentation and questionnaires. The data is processed by the formula percentages and standard deviations and analyzed by correlation of contingency coefficients. The results showed that (1) The level of maternal education were high for as many as 10 people or 50%, the categories are as many as 7 people or 35% and the low category as many as 3 people or 15%; (2) Logical mathematical intelligence which include high category with a score of 62.103 as many as three people, the medium category with a score of 44.697 to 62.103 as many as 13 people and low category with a score of  44.697 of 4 people and (3)There is a positive and significant relationship between mother's education level and logic-mathematical intelligence RA NU's 074 students Ronowijayan Ponorogo at a significance level of 5% with Φ0 table or 0.6000606 0.444 then H0 is rejected and Ha accepted.AbstrakPenelitian ini menjelaskan hubungan antara tingkat pendidikan ibu dan kecerdasan logika-matematika pada siswa RA Muslimat NU 074 Ronowijayan Ponorogo. Kajian ini dilaksanakan dengan pendekatan kuantitatif melalui studi dokumentasi dan angket. Datanya diolah dengan rumus persentase dan standar deviasi serta dianalisis dengan Korelasi Koefisien Kontingensi. Hasil penelitian menunjukkan bahwa (1) Tingkat pendidikan ibu yang termasuk kategori tinggi sebanyak 10 orang atau 50%, kategori sedang sebanyak 7 orang atau 35% dan kategori rendah sebanyak 3 orang atau 15%; (2) Kecerdasan logika-matematikayang termasuk kategori tinggi dengan skor 62,103 sebanyak 3 orang, kategori sedang dengan skor 44,697 – 62,103 sebanyak 13 orang dan kategori rendah dengan skor 44,697 sebanyak 4 orang dan (3) Terdapat hubungan yang positifdan signifikan antara tingkat pendidikan ibu dan kecerdasan logika-matematika siswa RA Muslimat NU 074 Ronowijayan Ponorogo pada taraf signifikansi 5% dengan Φ0 tabel atau 0.6000606 0.444 maka H 0 ditolak dan H a diterima.